Patient perspectives of care pathways for people with low back pain: A qualitative study. (December 2022) - Boyle, Eileen M.; Fary, Robyn E.; Lee, Samantha; Mikhailov, Anton; Evans, Kerrie; Rebbeck, Trudy; Beales, Darren J.
Abstract: Background: Low back pain (LBP) care pathways aim to enhance health outcomes through patient-clinician mutual decision-making and care coordination. However, challenges to successful translation into practice include patients' understanding, expectation, and acceptance of treatment and management strategies for LBP. This study explored patients' perspectives and/or experience of care pathways and their involvement in decision-making in primary care. Methods: A qualitative descriptive design was adopted. Semi-structured interviews were conducted with 14 participants with LBP recruited from the community. Inductive thematic analysis of the qualitative data was conducted within the design framework to enable a systematic comparison of experiences across participants and within individual cases. Results: Five themes described participant perspectives and understanding of care pathways: i) care pathways can guide decision-making; ii) familiarity with no and/or stepped care pathway, but preference for matched or blend of care pathways; iii) engaging in shared decision-making; iv) patient-related barriers to implementation; v) patient-related facilitators to implementation. Conclusions: Participants felt that existing care pathways did not meet their needs when pain persisted. Participants preferred matched or hybrid care pathways and suggested that implementation of such pathways should focus on addressing an individual's needs. Adopting a holistic approach, and clarity in shared decision-making, were deemed crucial for effective implementation of LBP pathways in practice. Consumer (patient) engagement in the design of LBP care pathways is recommended. Highlights: Incorporating patients' perspectives in the design of care pathways is recommended. Stepped care or unstructured care is commonly experienced in practice. Patients see value in care pathways that preserve a holistic approach. Effective shared decision-making is essential to support patients. Building shared decision-making strategies into pathway models may enhance implementation.